Optimalisasi Peran Kelompok Sadar Wisata (Pokdarwis) di Desa Lajing Kecamatan Arosbaya Kabupaten Bangkalan dalam Pengelolaan Obyek Wisata Pantai Pandela - Suud Maadi, Alan; Estu Harsiwi, Nova; Dwi Putra, Akbar; Safitri, Arda; Urrohmah, Aulia (Keris: Journal of Community Engagement, 2024)
The Role of Tourism Awareness Groups (Pokdarwis) in Management of Pandela Beach Tourism Objects. Currently, the tourism sector is one of the largest industries as well as a mainstay industry that can make a significant contribution to the economy for both the state and the region. So far, many new natural tourism potentials in Bangkalan have been discovered, one of which is a beach located in Lajing Village, Arosbaya District. Pandela Beach Tourism needs one of the roles of the Tourism Awareness Group (Pokdarwis). Because its function is to bridge the community so that it can realize its potentials. owned in managing and developing Pandela Beach natural tourism. This study aims to find out the role of the Tourism Awareness Group (Pokdarwis) in managing the Pandela Beach tourist attraction and what are the supporting and inhibiting factors in managing the Pandela Beach tourist attraction. There are several supporting factors, namely, the Pandela Beach tourist spot is the closest beach to the Suramadu Bridge and village officials who are very supportive. As for the inhibiting factors, the people's mindset in understanding tourism, limited sources of capital, and the management of the Tourism Awareness Group (Pokdarwis) themselves are still unable to be consistent in developing Pandela Beach attractions. The activities carried out in the research were socialization of tourism potential, revitalization of Pokdarwis, training on the abilities and skills of Pokdarwis members and the community in managing the tourism business sector. Suggestions that can be given are that there is a need for an icon or attraction for tourism, immediately realizing crafts to be traded so that they can be made special, and more controlling the role of each Pokdarwis member in managing Pandela Beach tourism.